2013
DOI: 10.1093/bja/aet122
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic regulation of cerebral blood flow in humans: a review

Abstract: Cerebral blood flow (CBF) is regulated by vasomotor, chemical, metabolic, and neurogenic mechanisms. Even though the innervation of cerebral arteries is quite extensively described and reviewed in the literature, its role in regulation of CBF in humans remains controversial. We believe that insufficient attention has so far been focused on the potential role of the innervation of the cerebral vasculature in cerebral autoregulation in humans. We have performed an extensive search and selection of available lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 257 publications
(126 citation statements)
references
References 59 publications
7
117
1
1
Order By: Relevance
“…It must be appreciated that factors other than arterial blood gas tensions are known to modulate the effectiveness of dCA, these include: (i) sympathetic activity; (ii) metabolite production; and (iii) perivascular innervation [35][36][37][38][39][40]. Our data do not allow us to comment on the role that these factors played in disrupting autoregulatory processes during maximal apnoea.…”
Section: Discussionmentioning
confidence: 69%
“…It must be appreciated that factors other than arterial blood gas tensions are known to modulate the effectiveness of dCA, these include: (i) sympathetic activity; (ii) metabolite production; and (iii) perivascular innervation [35][36][37][38][39][40]. Our data do not allow us to comment on the role that these factors played in disrupting autoregulatory processes during maximal apnoea.…”
Section: Discussionmentioning
confidence: 69%
“…Within a certain range of fluctuations in systemic blood pressure (i.e., mean arterial pressure 50-150 mmHg), the perfusion of the brain parenchyma is stabilized through different mechanisms, including myogenic vasomotor activity, chemical responses to hyper/hypocapnia, and alkalosis/acidosis, as well as neurogenic control involving the sympathetic nervous system. 32 Very little is known about the involvement of the thalamus in the neural network underpinning the neurogenic regulation of cerebral blood flow. Our speculation about a possible causative role of thalamic damage with regard to WMH accrual relies on a limited number of pioneering reports showing that some of the thalamic nuclei (e.g., the dorsomedial and the intrathalamic relay nuclei) are involved in cerebral blood flow regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, intense exercise can increase BBB permeability subsequent to a free radical-mediated impairment in CA, rendering the brain more susceptible to overperfusion and extracellular (vasogenic) edema; which has been shown to occur even in response to a more graduated incremental exercise test to exhaustion. 85 The direct effect of sympathetic nervous activity (SNA) on the cerebrovasculature remains controversial 28,105,106 and is further complicated in humans by the common inference of global SNA measures reflecting cerebral effects (e.g., via microneurography of SNA in the peroneal nerve versus noradrenaline spillover measurements 107 ). In fact, studies in sheep have indicated an inverse relationship between global and cerebral SNA; 108,109 thus, increases in muscle SNA may be reflected in a lowering of cerebral SNA.…”
Section: Optimizing Cerebrovascular Adaptation and Safety For High-inmentioning
confidence: 99%